Graph x^2+y^2+4x-2y=4

Math
x2+y2+4x-2y=4
Complete the square for x2+4x.
Tap for more steps…
Use the form ax2+bx+c, to find the values of a, b, and c.
a=1,b=4,c=0
Consider the vertex form of a parabola.
a(x+d)2+e
Substitute the values of a and b into the formula d=b2a.
d=42(1)
Cancel the common factor of 4 and 2.
Tap for more steps…
Factor 2 out of 4.
d=2⋅22⋅1
Cancel the common factors.
Tap for more steps…
Factor 2 out of 2⋅1.
d=2⋅22(1)
Cancel the common factor.
d=2⋅22⋅1
Rewrite the expression.
d=21
Divide 2 by 1.
d=2
d=2
d=2
Find the value of e using the formula e=c-b24a.
Tap for more steps…
Simplify each term.
Tap for more steps…
Cancel the common factor of (4)2 and 4.
Tap for more steps…
Factor 4 out of (4)2.
e=0-4⋅44(1)
Cancel the common factors.
Tap for more steps…
Cancel the common factor.
e=0-4⋅44⋅1
Rewrite the expression.
e=0-41
Divide 4 by 1.
e=0-1⋅4
e=0-1⋅4
e=0-1⋅4
Multiply -1 by 4.
e=0-4
e=0-4
Subtract 4 from 0.
e=-4
e=-4
Substitute the values of a, d, and e into the vertex form a(x+d)2+e.
(x+2)2-4
(x+2)2-4
Substitute (x+2)2-4 for x2+4x in the equation x2+y2+4x-2y=4.
(x+2)2-4+y2-2y=4
Move -4 to the right side of the equation by adding 4 to both sides.
(x+2)2+y2-2y=4+4
Complete the square for y2-2y.
Tap for more steps…
Use the form ax2+bx+c, to find the values of a, b, and c.
a=1,b=-2,c=0
Consider the vertex form of a parabola.
a(x+d)2+e
Substitute the values of a and b into the formula d=b2a.
d=-22(1)
Simplify the right side.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
d=-22⋅1
Divide 1 by 1.
d=-1⋅1
d=-1⋅1
Multiply -1 by 1.
d=-1
d=-1
Find the value of e using the formula e=c-b24a.
Tap for more steps…
Simplify each term.
Tap for more steps…
Raise -2 to the power of 2.
e=0-44⋅1
Multiply 4 by 1.
e=0-44
Divide 4 by 4.
e=0-1⋅1
Multiply -1 by 1.
e=0-1
e=0-1
Subtract 1 from 0.
e=-1
e=-1
Substitute the values of a, d, and e into the vertex form a(x+d)2+e.
(y-1)2-1
(y-1)2-1
Substitute (y-1)2-1 for y2-2y in the equation x2+y2+4x-2y=4.
(x+2)2+(y-1)2-1=4+4
Move -1 to the right side of the equation by adding 1 to both sides.
(x+2)2+(y-1)2=4+4+1
Simplify 4+4+1.
Tap for more steps…
Add 4 and 4.
(x+2)2+(y-1)2=8+1
Add 8 and 1.
(x+2)2+(y-1)2=9
(x+2)2+(y-1)2=9
This is the form of a circle. Use this form to determine the center and radius of the circle.
(x-h)2+(y-k)2=r2
Match the values in this circle to those of the standard form. The variable r represents the radius of the circle, h represents the x-offset from the origin, and k represents the y-offset from origin.
r=3
h=-2
k=1
The center of the circle is found at (h,k).
Center: (-2,1)
These values represent the important values for graphing and analyzing a circle.
Center: (-2,1)
Radius: 3
Graph x^2+y^2+4x-2y=4

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top